MONITORING AND ANALYSIS OF THE ACHIEVED RESULTS OF USING THE STEM OFFICES IN VELIKO TARNOVO REGION AFTER THE LAUNCH OF THE NATIONAL PROGRAM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Research has been done on the expectations and implementation of training in the newly built STEM centres under the current national program of the Ministry of Education and Science in Bulgaria. Initially, 16 schools on the territory of the Veliko Tarnovo region were selected for the construction of STEM centres with different orientations. They have been working for 2 years now, and based on observation and research among students and teachers, analysis and proposals for improving their effectiveness have been made. Based on the achieved results, the Ministry of Education and Science has expanded the national program for the construction of STEM centres and there will now be such in all schools, which eloquently speaks of their effectiveness and the increase in academic results. The results of conducting the training in the newly built centres and the satisfaction of the trainees and teachers are indicated.